The Role of Unsaturated Fatty Acid-Rich Dairy Products in Adipocyte Metabolism - Manuela Machado; Eduardo M. Costa; Sara Silva; Ana Maria Gomes; Manuela Pintado (Molecules, 2024)
This study investigated the fatty acid profile, permeability, and metabolic effects of a functional yogurt enriched with pomegranate oil, focusing on its impact on lipid metabolism and inflammatory responses. The yogurt’s fatty acid composition was primarily composed of long-chain polyunsaturated fatty acids (54.37%), followed by saturated (29.34%) and monounsaturated fatty acids (16.36%). During in vitro digestion, a shift in fatty acid profile was observed, with a decrease in polyunsaturated and saturated fatty acids and a slight increase in monounsaturated fatty acids due to hydrolysis. This study further analyzed fatty acid permeability across Caco-2/HT29-MTX monolayers and 3T3-L1 cell uptake, revealing higher permeability for saturated fatty acids than unsaturated ones. In 3T3-L1 cells, permeated fatty acids induced higher lipolysis and increased adiponectin secretion without affecting leptin levels. Cytokine analysis indicated a decrease in pro-inflammatory markers, such as MCP-1, and a significant increase in anti-inflammatory cytokines like IL-10, suggesting potential benefits in reducing obesity-related inflammation. These results underscore the role of functional yogurts enriched with polyunsaturated fatty acids as promising agents for modulating lipid metabolism and inflammatory responses.